Phenotypically resembling myeloid derived suppressor cells are increased in children with HIV and exposed/infected with Mycobacterium tuberculosis. Issue 1 (16th December 2016) - Du Plessis, Nelita; Jacobs, Ruschca; Gutschmidt, Andrea; Fang, Zhuo; van Helden, Paul D.; Lutz, Manfred B.; Hesseling, Anneke C.; Walzl, Gerhard
Abstract : Increased frequencies of M‐MDSC in peripheral blood of young children during HIV and TB exposure and infection, could endorse these cells as novel innate immune regulators of early life susceptibility to HIV/TB. Abstract : Increased disease susceptibility during early life has been linked to immune immaturity, regulatory T‐cell/TH2 immune biasing and hyporesponsiveness. The contribution of myeloid derived suppressor cells (MDSCs) remains uninvestigated. Here, we assessed peripheral MDSC in HIV‐infected and ‐uninfected children with tuberculosis (TB) disease before, during and after TB treatment, along with matched household contacts (HHCs), HIV‐exposed, ‐infected and ‐uninfected children without recent TB exposure. Serum analytes and enzymes associated with MDSC accumulation/activation/function were measured by colorimetric‐ and fluorescence arrays. Peripheral frequencies of cells phenotypically resembling MDSCs were significantly increased in HIV‐exposed uninfected (HEU) and M.tb ‐infected children, but peaked in children with TB disease and remained high following treatment. MDSC in HIV‐infected (HI) children were similar to unexposed uninfected controls; however, HAART‐mediated MDSC restoration to control levels could not be disregarded. Increased MDSC frequencies in HHC coincided with enhanced indoleamine‐pyrrole‐2, 3‐dioxygenase (IDO), whereas increased MDSC in TB cases were linked to heightened IDO and arginase‐1. Increased MDSC were paralleled by reduced plasma IP‐10 and thrombospondin‐2 levels in HEU and significantly increased plasma IL‐6 in HI HHC. Current investigations into MDSC‐targeted treatment strategies, together with functional analyses of MDSCs, could endorse these cells as novel innate immune regulatory mechanism of infant HIV/TB susceptibility.